QTL mapping of grain yield and yield components in pure lines derived from Roshan × Falat bread wheat varieties (Triticum aestivum L.) under limited irrigation condition - Maryam Dorrani Nezhad (مجله بیوتکنولوژی کشاورزی, 2016)
In order to identify QTLs associated with grain yield and yield components in Bread Wheat under limited irrigation condition using ICIM method, 305 pure lines (F8)  generation of bread wheat derived from cross between Roshan and Falat along with four standard cultivar namely Roshan, Falat, Mahdavi and Shahpasand, were evaluated based on Augmented design. Stress treatment was cut off irrigation at heading stage. Grain yield and other agronomic traits were measured as the phenotypic traits. The result revealed that there are transgressive segregations for all under studied traits. A genetic map was constructed with 808 DArTs markers which these markers covered 5395.69 CM of the genome with the average of 7CM. In total 24 QTLs were identified on 13 chromosomes with additive effect for 12 traits. Four QTLs had R2>10. The qAL6A was identified for awn length that explained 26.24 percent of the total phenotypic variance. qPL4B was found for peduncle length and contributed 17.15 percent of phenotypic variance and is locating at the same interval with flag leaf sheath length QTL. This phenomenon could be due to polytrophic or due to linkage effect of those genes which control these two traits. Major QTLs associated with grain yield and yield components under limited irrigation condition after validation can be used in plant breeding programs and marker-assisted selection in order to produce tolerant and high performance wheat varieties.